Surface functionalization of inorganic nanoparticles with ligands: a necessary step for their utility - Bhattacharjee, Kaustav; Prasad, Bhagavatula L. V. (Chemical Society Reviews, 2023)
The importance of organic ligands in protecting inorganic nanoparticles and thus imparting the needed stabilization as colloidal dispersions was realised many years ago. Currently, the rational preparation of such nanoparticles with designed organic molecules/ligands resulting in the formation of functional nanoparticles (FNPs) that are tuned for a specific application is an area of immense research interest. The preparation of such FNPs for a desired application requires a clear understanding of the interactions at the nanoparticle (NP)-ligand and ligand-solvent interfaces, and demands a deep appreciation of the surface science and coordination chemistry. In this tutorial review, we briefly explore the evolution of surface-ligand chemistry and inform the readers that, apart from protecting the surface, ligands can modulate the physico-chemical properties of the underlying inorganic NPs as well. This review further presents the design principles for the rational preparation of such FNPs, where one or more ligand shells can be added to the nanoparticle surface, thereby improving the adaptability and amenability of the NP exterior towards the environment in which they are present, as required for a specific application.